1996
DOI: 10.1108/01437739610130519
|View full text |Cite
|
Sign up to set email alerts
|

The darker side of the entrepreneur

Abstract: Investigates the role of the entrepreneurial personality in the global economy, based on consulting work carried out on one fast‐growing small business, Distant Learning Ltd. Shows how the “dark side” of a personality can affect others. Concludes that self‐awareness is the answer to problems in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 2 publications
1
29
0
Order By: Relevance
“…McKenna () suggests that ‘entrepreneurs have pervasive fears of being victimized; they are continually scanning their environment for something to confirm their suspicions …. If we look hard enough there is always, somewhere, some confirmation’ (Kets de Vries, , pp.…”
Section: Explaining Practice Persistencementioning
confidence: 99%
“…McKenna () suggests that ‘entrepreneurs have pervasive fears of being victimized; they are continually scanning their environment for something to confirm their suspicions …. If we look hard enough there is always, somewhere, some confirmation’ (Kets de Vries, , pp.…”
Section: Explaining Practice Persistencementioning
confidence: 99%
“…Dickers, Jansen, de Lange, Vinkenburg and Kooij (2010) found that an entrepreneurial personality is associated with increased engagement and thereby better performance. McKenna (1996) concluded that entrepreneurs can sometimes negatively affect performance of a firm through the "dark side" of their personality. Julian & Ahmed (2012) pointed out that one way for entrepreneurs to enhance their performance is to expand their business towards export markets.…”
Section: Linking Personality and Performancementioning
confidence: 99%
“…Dickers, Jansen, de Lange, Vinkenburg and Kooij (2010) found that an entrepreneurial personality is associated with increased engagement and thereby better performance. McKenna (1996) concluded that entrepreneurs can sometimes negatively affect performance of a firm through the "dark side" of their personality. Julian & Ahmed (2012) pointed out that one way for entrepreneurs to enhance their performance is to expand their business towards export markets.…”
Section: Linking Personality and Performancementioning
confidence: 99%